Can we identify the heart rate deflection point and rating of perceived exertion threshold during the Yo-Yo Intermittent Recovery Test level 1 in university basketball players? A pilot study - Szymczak Conde, J. H.; Souza, G. C.; de Lima Costa, P.; Novack, L. F.; Osiecki, R. (Human Movement, 2016)
The aim of the study was to identify the heart rate deflection point (HRDP) and the rating of perceived exertion (RPE) threshold (DmaxRPE) during the Yo-Yo Intermittent Recovery Test level 1 (Yo-Yo IR1) in university basketball players. Methods. Eleven male university basketball athletes performed two incremental tests, interspersed by seven days, in a random crossover pattern: (1) the treadmill test with the initial velocity of 6 km ? h-1, increments of 1 km ? h-1 each 2 minutes, and pauses of 15 seconds between the stages; (2) the Yo-Yo IR1. Results. During the Yo-Yo IR1, the HRDP and the DmaxRPE were identified only in six and seven subjects, respectively. In the treadmill test, the HRDP and the DmaxRPE were found in 11 and 10 individuals, respectively. Additionally, there were no differences between the velocity of occurrence of the HRDP and the DmaxRPE recognized in the treadmill test and in the Yo-Yo IR1 (p > 0.05). Conclusions. The results suggest that if the goal is to determine aerobic capacity by the HRDP and the DmaxRPE, Yo-Yo IR1 should not be used. Instead, the treadmill test is a reliable tool.